First antineutrino energy spectrum from 235U fissions with the STEREO detector at ILL*Stereo Collaboration, http://www.stereo-experiment.org. (20th May 2021) - Almazán, H; Bernard, L; Blanchet, A; Bonhomme, A; Buck, C; del Amo Sanchez, P; El Atmani, I; Labit, L; Lamblin, J; Letourneau, A; Lhuillier, D; Licciardi, M; et al.
Abstract: This article reports the measurement of the 235 U-induced antineutrino spectrum shape by the Stereo experiment. 43 000 antineutrinos have been detected at about 10 m from the highly enriched core of the ILL reactor during 118 full days equivalent at nominal power. The measured inverse beta decay spectrum is unfolded to provide a pure 235 U spectrum in antineutrino energy. A careful study of the unfolding procedure, including a cross-validation by an independent framework, has shown that no major biases are introduced by the method. A significant local distortion is found with respect to predictions around E ν ≃ 5.3 MeV. A Gaussian fit of this local excess leads to an amplitude of A = 12.1 ± 3.4% (3.5 σ ).